TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN AKTA DILUAR WILAYAH KERJANYA TERAIT AKIBAT HUKUM ATAS PELANGGARAN UNDANG-UNDANG JABATAN NOTARIS DAN KODE ETIK NOTARIS. - Sudomo, Darasati Damarani; Franciska, Wira; Widyanti, Amelia Nur (LPPM Institut Pendidikan Nusantara Global, 2023)
Responsibilities of notaries in making deeds outside their work area investigate the obligations and roles of Notaries when making deeds outside their work area. Related legal consequences for violation of the Notary Office Act and the notary Code of Ethics investigate the legal consequences that a notary may face if he violates the Notary Office Law and the notary Code of ethics. This study uses two theories of law, namely The Theory of legal consequences and liability theory. The method used in this research is normative juridical research, specifically a library law research or secondary data with primary, secondary and tertiary legal sources. As for the research approach used in this case the legislation relating to land acquisition and the method of collecting the legal materials are carried out by identifying and taking an inventory of positive law, journals and other legal sources. The method used in analyzing the legal materials (interpretation) is to get views on the public interest is ultimately owned by either private ownership or management. to get legal certainty and legal construction method. The result of this study is the deed outside the territory of the Notary is valid as evidence, can be canceled if it is defective and disputed, only by the party in the deed. The act of abrogation occurs as an act under hand. The notary is responsible civil and administrative, can sanction fees, damages, interest, warning, dismissal, or dismissal. Violation of Article 17 paragraph (1) letter a uujn-P triggers civil and administrative liability, lawsuit to the General Court. If the deed is void, the Notary is charged fees, damages, and interest. Administrative sanctions are established by the Supervisory Board of Notaries. Although not a criminal offense, notaries are bound by civil, administrative, and professional code of ethics liability. The Code provides for obligations, prohibitions, exceptions and internal sanctions